Construct-Oriented or Goal-Motivated? Interpreting Test Preparation of a High-Stakes Writing Test From the Perspective of Expectancy-Value Theory - Xu, Shasha (Frontiers in Psychology, 2022)
Of the many possible individual factors bearing on test preparation, one is how individuals’ motivational and cognitive perceptions affect test-driven preparation practices. This study reports an investigation into test preparation of a high-stakes writing test from the perspective of expectancy-value theory. Undergraduate students (n = 623) on their test preparation for the writing tasks of China’s Graduate School Entrance English Examination (GSEEE) were recruited voluntarily from 11 universities in mainland China. The perceptions of GSEEE test takers, which included goal, task value, task demand, and expectation of success, were identified. Five types of preparation practices were identified for the GSEEE writing tasks: memorizing practice, test familiarization, comprehensive learning, skills development and drilling practice. Structural equation modelling revealed that the expectancy-value model held up well for the paths from test takers’ perceptions to test-driven preparation practices, which were not construct-oriented but goal-motivated. The GSEEE test takers’ goal, determined by the high-stakes nature of admission test, explained their motivation and determined their behavior towards test preparation. Results also indicated that task demand was inadequate to be termed a strong factor in affecting test preparation. As such, the findings of this study offer evidence regarding how an expectancy-value model fit into test preparation mechanism and provide insights into the nature and scope of test preparation for high-stakes writing tests.